Association between gestational weight gain and perinatal outcomes among women with gestational diabetes mellitus - Guo, Zize; Lin, Lihua; Dong, Jiayi; Lin, Juan (Frontiers in Endocrinology, 2025)
ObjectiveThis study identifies the optimal gestational weight gain (GWG) range for women with gestational diabetes mellitus (GDM) in singleton pregnancies and examines the relationship between GWG patterns and perinatal outcomes.MethodsWe included 18,548 pregnant women diagnosed with GDM via a 75g glucose tolerance test at Fujian Maternal and Child Health Hospital from 2011 to 2022. Data on demographics, GWG, delivery details, and maternal and infant outcomes were collected. Subjects were divided into training and validation sets (7:3 ratio) and classified by pre-pregnancy BMI: underweight, normal weight, overweight, and obese. Logistic regression in the training set was conducted to determine optimal GWG for each group, and examined the relationship between adverse outcomes and the Institute of Medicine(IOM), Chinese nutrition society(CNS), and study-derived (AOR) standards in the validation set.ResultsAmong participants, 17.0% pregnant women gained insufficient GWG, 49.2% gained appropriate GWG, and 33.9% with excessive GWG. The optimal GWG for underweight, normal weight, overweight, and women with obesity were 12-14 kg, 8-14 kg, 6-10 kg, and 2-4 kg, respectively. Insufficient GWG in IOM and AOR standard increased composite adverse outcomes among underweight women. Normal weight: Insufficient GWG per CNS and AOR increased composite adverse outcomes; excessive GWG per all standards increased adverse outcomes. Insufficient GWG per all standards reduced the risk of small-for-gestational-age (SGA) infants, while excessive GWG increased the risk of large-for-gestational-age (LGA) infants, gestational hypertension, and cesarean section. Overweight: Excessive GWG per CNS and AOR increased composite adverse outcomes; excessive GWG per all standards increased the risk of cesarean delivery. Obese: Insufficient GWG per IOM and CNS increased composite adverse outcomes.ConclusionGWG significantly influences adverse pregnancy outcomes. Compared to IOM guidelines, CNS recommendations and study-derived GWG ranges are more suitable for Chinese women with GDM in singleton pregnancies.